Aplikasi Nilai Online, Pembayaran SPP, dan Absensi Berbasis Website di SMP Islam Al-Ikhlas Jakarta Selatan - Marliana Budhiningtias Winanti; Muhammad Dhiyauddin (Program Studi Manajemen Informatika, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia, 2019)
Lack of publications to deliver online value information makes Al-Ikhlas Islamic Junior High School has a weakness in disseminating information to parents in Al-Ikhlas Islamic Junior High School South of Jakarta in the publicized value for children - her son, because the conventional media used by teachers Al-Ikhlas Islamic Junior High School South of Jakarta only form of notes on ledger Master Data Master. Data collection methods used were observation and interviews, with observation and interviews are expected to obtain sufficient data for the manufacturing of value-line application will be made for Al-Ikhlas Islamic Junior High School south of Jakarta. The approach used is object-oriented approach (Object Oriented). By designing a web- based online application value in SMP Islam Al-Ikhlas South Jakarta, is expected to improve efficiency and streamline the process of accessing information and maximize the delivery of academic information which will be aimed at students, teachers and parents. With value-based online application he designed the website in Al-Ikhlas Islamic Junior High School South of Jakarta, is expected to also school - other schools will make this application in every school.